Structural-phase transitions and state function in unstable convective medium - Gushchin, I.V.; Kirichok, A.V.; Kuklin, V.M. (Вопросы атомной науки и техники, 2015)
Convection in a thin layer of liquid (gas) with temperature independent viscosity between poorly heat conducting boundaries is studied within framework of the Proctor-Sivashinsky model. We have shown by numerical simulation of the Proctor-Sivashinsky model that the state with certain topology can be described by the state function, which is the sum of squared mode amplitudes of spatial temperature spectrum. The transitions between these states are characterized by splashes in time-derivative of this function and different meta-stable structures, corresponding to different values of the state function have different visually distinguishable topologies. Конвекцію в тонкому шарі рідини (газу) між поверхнями, що недостатньо добре проводять тепло, розглянуто в умовах придатності моделі Проктора-Сівашинського за відсутністю залежності в’язкості від температури. З використанням числового моделювання показано, що кожен стан може бути представлений за допомогою функції стану, що дорівнює сумі квадратів мод просторового спектра температури на поверхні. Перехід між станами характеризується значенням похідної за часом від функції станів. Різниця між метастабільними станами, які відрізняються топологією, визначається різними значеннями функції стану. Конвекция в тонком слое жидкости (газа) между плохо проводящими тепло поверхностями рассмотрена в условиях применимости модели Проктора-Сивашинского при отсутствие зависимости вязкости от температуры. С помощью численного анализа показано, что каждое состояние может быть описано с помощью функции состояния, которая равна сумме квадратов мод спектра пространственного распределения температуры на поверхности. Переход между состояниями характеризуется изменением производной по времени от этой функции. Различие между метастабильными состояниями, которые отличаются топологией, определяется разными значениями функции состояния.